Comparing models for forecasting the yield curve - Marco Shinobu Matsumura; Ajax Reynaldo Bello Moreira (Institute for Applied Economic Research (ipea), 2015)
The evolution of the yields of different maturities is related and can be described by a reduced number of commom latent factors. Multifactor interest rate models of the finance literature, common factor models of the time series literature and others use this property. Each model has advantages and disadvantages, and it is an empirical matter to evaluate the performance of the approaches. This exercise compares 4 alternative models for the term structure using 3 different markets: the Brazilian domestic and sovereign market and the US market.
Keywords: C13; C32; C53; E43; E44; E47; G12; G13; 330